H3PW12O40 synergized with MCM-41 for the catalytic nitration of benzene with NO2 to nitrobenzene. Issue 89 (27th September 2015) - You, Kuiyi; Deng, Renjie; Jian, Jian; Liu, Pingle; Ai, Qiuhong; Luo, He'an
<x xml:space="preserve">Abstract</x> In this work, NO2 as a nitration agent and the supported HPW/MCM-41 as a synergistic catalyst to replace traditional nitric acid and sulfuric acids were employed to catalyze benzene nitration to nitrobenzene.